Investigation of Gold Nanostructures on Silicon Using Electrochemical Deposition Method - Faisal, Abdul-Qader Dawood; Lafta, Sadek Hani (Al-Nahrain Journal of Science, 2013)
Nanostructures of gold electrodeposited on silicon (100) substrate with two electrode homemade cell were investigated. In this paper we report our experimental results of gold-electroplating using a sulfite-based electrolyte instead of toxic gold-cyanide. The used electrolyte was safe and friendly environmental. Film thickness as a function of current density and deposition rate were calculated using gravity method. An empirical formula was satisfied the expected deposition thicknesses. Deposition rate of ≈ 5-40nm/ min was achieved. Au (111) structure for gold nanofilm was characterized by XRD. Morphology of gold film deposited was investigated with AFM. Morphology of Au thin films on silicon shows nanosize particles after annealing process at 600°C.